2021
DOI: 10.3390/ijerph18168746
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Delta Aminolevulinic Acid Dehydratase (ALAD) Gene and Symptoms of Chronic Mercury Exposure in Munduruku Indigenous Children within the Brazilian Amazon

Abstract: Genetic polymorphisms involved in mercury toxicokinetics and toxicodynamics may be associated with severe mercury toxicity. This study aimed to investigate the impact of an ALAD polymorphism on chronic mercury exposure and the health situation of indigenous children from the Brazilian Amazon. One-hundred-and-three indigenous children (under 15 years old) were included and genotyped (rs1800435) using a TaqMan validated assay. The mean age was 6.6 ± 4.5 years old, 60% were female, 49% presented with anemia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…According to the Agency for Toxic Substances and Disease Registry (ATSDR 2022), the signs and symptoms of Hg intoxication include primarily neurological and motor effects, but health effects extend to other systems such as kidney damage, cardiovascular, immunological and developmental disorders, especially reported in accidental or occupational settings.Concerning chronic environmental exposure, the psychomotor performance showed impairments in Amazonian riverine populations exposed to MeHg(Dolbec et al 2000). High prevalence of symptoms such as visual changes, memory de cit, amyotrophy(Perini et al 2021), as well as failures in tests or exams involving sensory and motor skills(Corbett et al 2007) have been reported in chronically exposed Amazonian populations to Hg, consistent with the ndings in the present study.…”
supporting
confidence: 90%
“…According to the Agency for Toxic Substances and Disease Registry (ATSDR 2022), the signs and symptoms of Hg intoxication include primarily neurological and motor effects, but health effects extend to other systems such as kidney damage, cardiovascular, immunological and developmental disorders, especially reported in accidental or occupational settings.Concerning chronic environmental exposure, the psychomotor performance showed impairments in Amazonian riverine populations exposed to MeHg(Dolbec et al 2000). High prevalence of symptoms such as visual changes, memory de cit, amyotrophy(Perini et al 2021), as well as failures in tests or exams involving sensory and motor skills(Corbett et al 2007) have been reported in chronically exposed Amazonian populations to Hg, consistent with the ndings in the present study.…”
supporting
confidence: 90%
“…The genotyping analysis of the GSTP1 (chr11:67585218) A>G (rs1695) missense variant was performed using a TaqMan allelic discrimination assay (C_3237198_20) by a 7500 Real-Time System (Applied Biosystems, Foster City, CA, USA), as previously described [ 14 ] and the GSTP1 A>G allele frequency and genotype distribution were derived by gene counting.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed an association between levels of mercury in the body and genetic polymorphisms, either conferring higher body levels of Hg or signs and symptoms of intoxication from this exposure [ 9 , 10 , 11 , 12 ] or providing protection against these effects [ 9 , 11 , 13 ]. Recently, the delta aminolevulinic acid dehydratase ( ALAD ) 177 C>G (rs1800435) polymorphism was identified in two indigenous children from the Brazilian Amazon, who showed elevated Hg levels (>9 µg/g), exceeding the reference limit (≥6.0 µg/g), and several neurological symptoms such as visual field alterations, memory deficit, distal neuropathy and toe amyotrophy [ 14 ]. Therefore, the study of polymorphisms in genes involved in MeHg metabolism is of great importance [ 4 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplification was performed in 8 μL reactions with 1 μL of template DNA (~10 ng/μL), 1 × TaqMan Universal Master Mix, 1 × each primer, and probe assay. Thermal cycling was initiated with a first denaturation step of 10 min at 95 °C, followed by 40 cycles of denaturation at 92 °C for 15 s and annealing at 60 °C for 1 min, as previously described [ 20 ]. Each reaction used two standardized positive controls of each polymorphism genotype to assure genotyping quality.…”
Section: Methodsmentioning
confidence: 99%